2022
DOI: 10.1002/jcsm.13095
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body mass index, weight loss and overall survival in patients with advanced lung cancer

Abstract: Background Weight loss (WL) has been associated with shorter survival in patients with advanced cancer, while obesity has been associated with longer survival. Integrating body mass index (BMI) and WL provides a powerful prognostic tool but has not been well‐studied in lung cancer patients, particularly in the setting of clinical trials. Methods We analysed patient data (n = 10 128) from 63 National Cancer Institute sponsored advanced non‐small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Subsequent internal validation cohorts demonstrated that the IBI is a simple, effective, reproducible biomarker for the prognostic assessment of patients with NSCLC. Weight loss is an important factor in the assessment of cachexia and prognostic evaluation of patients with cancer 25 . However, the clinical assessment of weight loss depends mainly on self‐reporting of cancer patients, and weight loss data are often lacking clinically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent internal validation cohorts demonstrated that the IBI is a simple, effective, reproducible biomarker for the prognostic assessment of patients with NSCLC. Weight loss is an important factor in the assessment of cachexia and prognostic evaluation of patients with cancer 25 . However, the clinical assessment of weight loss depends mainly on self‐reporting of cancer patients, and weight loss data are often lacking clinically.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is not only a marker of inflammation but also has many key pro‐inflammatory properties. CRP can induce the initiation of endothelial and smooth muscle cells and promote the expression of adhesion molecules, chemoattractants and vascular endothelial growth factor, which are essential for tumour invasion 25,26 . In addition, some studies have found that CRP can directly affect the function of immune active cells, thereby affecting the body's cytotoxic immune response and promoting tumour immune escape 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive investigations on this topic have been conducted in large cohorts after adjusting potential confounders such as smoking and race. Several studies also included additional details to categorize obesity, for example, using BMI trajectories and metabolic obesity as phenotype (1)(2)(3)(4)(5)(6). Although the effect of obesity on small cell lung cancer and lung squamous cell carcinoma (LUSC) remains inconclusive, a consistent inverse effect of obesity on lung adenocarcinoma (LUAD) were observed across studies, especially for those patients receiving immune checkpoint inhibitor treatments.…”
Section: Introductionmentioning
confidence: 99%